(untitled) (Olhar de Professor, 2023)
This work is of a qualitative nature and brings an autobiographical account of experience in teaching Higher Education in a private for-profit institution, during law, in Minas Gerais, for the corpus of analysis of scientific research. With the aim of discussing the difficulties of the HEI in times of social distancing and lockdowns, the commitment of education professionals and the lack of motivation shown by students, and the positive points surrounding these issues. The study is situated within the scope of (auto)biographical research in the right to education and has the autobiographical narrative as an investigation method. The study reveals that emergency remote teaching is far from the ideal type of university education, however, given the categorical factors that make face-to-face classes unfeasible during the COVID-19 pandemic, this mode of teaching was the alternative of higher education and brought about deficiencies that were hidden, in the same way new Information and Communication Technologies emerged that have a positive reflection on the teaching and learning processes.